EVALUATION OF SOME INSECTICIDES AGAINST FRUIT AND SHOOT BORER, EARIAS VITTELLA (FAB.) IN SEED PRODUCTION OF OKRA ( OF OKRA (ABELMOSCHUS ESCULENTUS ABELMOSCHUS ESCULENTUS) - BASAVARAJ; A. S, CHANNAVEERSWAMI; S, LAKKUNDI (The Bioscan, 2016)
This study was carried out to determine the efficacy of seven insecticides viz., lamb-dacyhalothrin,imidacloprid, B-Cyfluthrin, cypermethrin, profenofos, dimethoate and indoxacarb against the shoot and fruit borer, Earias vittella (Fabricius) on okra cultivar Arka Anamika during kharif season of 2011 and 2012. The treatment with lambda-cyhalothrin recorded significantly minimum (18.44% and 10.03%) per cent fruit damage per plant and per cent seed damage per fruit which was at par with the indoxacarb (19.12% and 9.86%) and dimethoate 30% EC 2ml/litre (22.70% and 12.34%) in pooled data. Significantly maximum (57.58% and 31.31%) per cent fruit damage per plant and per cent seed damage per fruit were recorded with imidacloprid 40g a.i/ha in pooled data. The highest seed yield per hectare was observed with application of lamb-dacyhalothrin (1548kg), indaxocarb (1474kg) and dimethoate (1435kg) and the lowest was with imidacloprid (618kg) in pooled data. Except imidacloprid, all insecticides proved significantly effective in controlling E. vittella infestation. The highest seed yield with high quality was recorded in the foliar sprays of Lamda-cyhalothrin 30g a.i/ha, for the control of fruit borer incidence in seed production of okra, therefore one among these three chemicals viz., Lamda-cyhalothrin 30g a.i/ha, Indoxacarb 14.5% 0.25ml/litre and Dimethoate 30% EC 2ml/litre can be made use